Piles and pile foundations - Viggiani, Carlo; Russo, Gianpiero (Spon Press, 2012)
This book provides an overview of present design practice of piled foundations, under both vertical and horizontal loads, and then a presentation of recent advances in the analysis and design of piled rafts. Altogether it forms a thorough guide to the design and analysis of efficient and effective piled rafts, and it also serves as a useful design handbook for traditional pile foundations